The 2dF QSO Redshift Survey - VIII. Absorption systems in the 10k catalogue - Outram, P; Smith, R; Shanks, T; Boyle, B; Croom, S; Loaring, N; Miller, L (2001)
We examine the highest S/N spectra from the 2QZ 10k release and identify over 100 new low-ionisation heavy element absorbers; DLA candidates suitable for higher resolution follow-up observations. These absorption systems map the spatial distribution of high-z metals in exactly the same volumes that the foreground 2QZ QSOs themselves sample and hence the 2QZ gives us the unique opportunity to directly compare the two tracers of large scale structure. We examine the cross-correlation of the two populations to see how they are relatively clustered, and, by considering the colour of the QSOs, detect a small amount of dust in these metal systems.